ASSESSING THE BUSINESS INCUBATORS’ PERFORMANCE REFERRING THE LOCAL DEVELOPMENT IN ITALY - Christian Corsi; Daniela Di Berardino (European Scientific Journal, ESJ, 2014)
Literature assign to business incubators an important role in promoting innovative entrepreneurship and economic growth. This study investigates the relationship between incubators performance and local development in Italy, focusing on those characteristics of regional contexts that enhance the role of incubators. Using a sample of 162 incubators, the regional economic index for 18 regions and the performance data for 405 new technology ventures located within these regions, we show that the local context features play a positive effect on the incubators performance. The nature of founders team of incubators is also important to implement effective entrepreneurial initiatives, while the sectorial specialization isn’t an essential requirement for the success of NTVs. Different factors of local context contribute positively to generate an environment that enhance the incubators’ activities.